A System for Managing Staff and Quality of Dementia Care in Assisted Living Facilities. Issue 8 (18th July 2018) - Simmons, Sandra F.; Coelho, Chris S.; Sandler, Andrew; Schnelle, John F.
Abstract : Objectives: To describe a staff management and quality improvement system implemented in an assisted‐living facility (ALF) that provides dementia care. Design: Prospective quality improvement project over 13 consecutive months. Setting: One ALF that provides dementia care services. Participants: ALF residents with dementia (N=57). Intervention: A staff management and quality improvement system was implemented for 3 aspects of daily care: morning and evening activity of daily living (ADL) care, nutritional care, and activity engagement. Measurements: Supervisory staff monitored the quality of daily care processes of all residents and direct care staff using standardized observations. Observational data were summarized into quality measures for each of the 3 daily care areas and ranged from 0% to 100%, with a higher score indicative of better quality. These quality measures were shared with direct care staff in weekly huddles at which feedback was provided about areas in need of improvement. The management team also reviewed the data weekly to discuss strategies for improvement. Results: The quality measures in each of the 3 areas improved or remained consistently high over the 13 study months: morning and evening ADL care (83–96%), quality nutritional of care during meals (74–95%), activity engagement (69–97%). Conclusion: A staff management and quality improvement system that relies on standardized observations of quality of care, weekly review by managers, and feedback to direct care staff informs areas in need of improvement and supports consistent implementation of quality of care over time for ALF residents receiving dementia care.